ISLAMIC INTEGRATION IN ENGLISH LANGUAGE TEACHING - Abdul Basith; Ahmad Syafi'i; Yiyin Isgandi (STKIP AL HIKMAH SURABAYA, 2022)
The Islamic integration as unit in learning and teaching is important. It can make civil society generations which applied the Islamic integration in students’ life well. integration learning is not only developed to achieve goals holistic learning as stated in concerning National Education Standards, expected by students as well could:1. Improve the understanding of concepts learned more meaningful. 2. Develop skills in finding, processing, and utilize information. 3. Develop positive attitudes, good habits and values noble needed in life. 4. Develop social skills such as cooperation, tolerance, communication, and respecting the opinions of others. 5. Increase passion in learning. 6. Have activities that are in accordance with interests and needs.